A combined experimental-numerical analysis of a novel deformable sandwich structure for morphing wing applications. (November 2021) - Hajarian, Amin; Zakerzadeh, Mohammad Reza; Salehi, Hamid; Baghani, Mostafa
In this paper, a new flexible sandwich structure is introduced, which can be employed in morphing aircrafts capable of intelligently changing their shape in different flight conditions. To accomplish this goal, first, a review of the various ideas in the literature is presented. In the following, features of the proposed structure and its differences from other ideas are expressed. Then, the process of fabrication and the various stages of shaping the structure are described. In an aircraft with variable wings camber, the deformable section can be assumed to be a cantilever beam. Thus, samples of the proposed structure are fabricated as the cantilever beam and are tested as tip-loaded beams. Since the numerical analysis of the new structure involves the recognition of the mechanical behavior of its components, a comprehensive review of the mechanical behavior of each component of the structure is performed. Afterwards, the numerical method is utilized to model samples of the structure, and the changes in the samples' deformation are examined under different loads. According to the observation of the broken samples, to arrive at more accurate numerical results, a distribution for the cavities, caused by the manufacturing process, is considered. Finally, with the same assumptions, another sample is analyzed, and it is shown that the results of the second model are consistent with experimental results.